Determinant Factors of Medication Compliance in DM2 Patients: A Systematic Review - Faza Khilwan Amna; Chatila Maharani; Ari Yuniastuti; Sri Ratna Rahayu; Evi Widowati (Indonesian Journal of Global Health Research, 2025)
Type 2 Diabetes Mellitus (DM2) is a chronic disease that requires high compliance in treatment to prevent complications. However, many DM2 patients are not compliant in undergoing drug therapy, which can hinder the effectiveness of treatment. Various factors have been identified as determinants of patient compliance, including demographic factors, knowledge, social support, and technology utilization.This study aims to analyze factors that influence medication adherence in DM2 patients based on a systematic review of several studies that have been conducted. The method used in writing this article is a literature review study with a systematic review method. The articles reviewed were obtained through searches on Google Scholar, Pubmed, Proquest, and ScienceDirect in the period 2015-2025 with the search keywords being Type 2 Diabetes Mellitus, Medication Compliance, Compliance Factors, Medication Supervisors . By using PRISMA, from 10,697 articles found, 10 journal articles were obtained to be reviewed. Based on the analysis of several studies, factors that have a significant influence on patient compliance in taking medication are the level of knowledge (p = 0.002), family support (p = 0.000; PR = 8.17 ) , and support from health workers (p = 0.000; PR = 6.10). Social Marketing, Frailty Syndrome and Age were also found to have a relationship with DM medication compliance. In addition, the use of technology such as medication reminder applications (PMO) has been shown to help improve patient compliance in undergoing DM2 therapy. Compliance of DM2 patients in undergoing drug therapy is influenced by various factors, including level of knowledge, social support, social marketing, age , frailty syndrome, and use of technology. Therefore, strategies to improve compliance must involve an educational approach, strengthening the role of families and health workers, and utilizing digital-based technology to increase the effectiveness of DM2 therapy.